To the knowledge of the subgenus Phrator Semenov, 1922 of the genus Omophron Latreille, 1802 (Coleoptera: Carabidae) - Anichtchenko, Alexander; Valainis, Uldis (Zootaxa, 2024)
The species of the subgenus Phrator Semenov, 1922 are reviewed, with six species now recognized. One species is downgraded to subspecies: O. multiguttatum depressum Klug, 1853 stat. nov. Some new synonymies are proposed Omophron variegatum boiteli Alluaud, 1935 syn. n. = Omophron variegatum sardoum Reitter, 1907 syn. n. = Omophron variegatum seurati Alluaud, 1935 syn. n. = Omophron (Phrator) variegatum Olivier, 1812; Omophron (Phrator) ethiopiensis Valainis, 2016 syn. nov. = O. multiguttatum (s.str) Chaudoir, 1850; and Omophron (Phrator) alluaudi Dupuis, 1913 syn. n. = O. vittulatum Fairmaire, 1894. The variability of all the treated species is discussed. A key to the species, together with new distributional data, maps of distribution, illustrations of the habitus and of the most important features are provided.